Pemanfaatan Arang Aktif Biji Kapuk (Ceiba Pentandra L.) sebagai Adsorben Logam Timbal (Pb) - Wahyuni, Sri; Ningsih, Purnama; Ratman, Ratman (Universitas Tadulako, 2016)
Lead is a heavy metal that has been a problem particulary in the aquatic environment. This reseach is an effort to reduce these problems by using adsorption method that utilizes an adsorbent of cotton seeds to Pb. Cotton seeds were chemically activated trough the process using a solution of 85% H3PO4. This study aims to determine the optimum weight of activated charcoal an adsoption capacity in optimum condition by using two parameter variations of weight of 0,3; 0,6; 0,9; 1,2 and 1,5 grams and Pb concentration of 10, 20, 30, 40 and 50 ppm by using a contact time of 30 minutes. Pb concentration was measured using a spectrophotometer spectro-direct. The result obtained that optimum weight of active charcoal cotton seeds was 1,2 grams with a percentage of 97,76% uptake an adsorption capacity in optimum condition Pb was 0,05 mg/mg activated charcoal.